2012
DOI: 10.5559/di.21.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal Beliefs and Personality Traits in Croatia

Abstract: The goal of this study was to assess the relationship between the Five Factor Model of personality and the belief in the paranormal. Participants (N=307) were students from the University of Zagreb, Croatia. The measures used were the IPIP version of the Five Factor Model questionnaire (Goldberg et al., 2006) along with the Revised Paranormal Belief Scale (Tobacyk, 1988). The factor analysis of the latter yielded three previously unreported paranormal belief dimensions named: General paranormal belief, Traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
5
2
Order By: Relevance
“…For divergent validity, there were only negligible correlations (r's between 0 and 0.30) to all other measures, providing more evidence that the NEBS is not measuring other constructs. Interestingly, other studies evaluating personality traits and paranormal beliefs have been mixed 62,63 , with some studies observing positive correlations with neuroticism 64,65 (unlike our study which found a negligible negative correlation) and others not finding any correlations [65][66][67] . The NEBS reliability and internal consistency was also demonstrated through high Cronbach's alphas for both subscales in two different samples.…”
Section: Discussioncontrasting
confidence: 87%
“…For divergent validity, there were only negligible correlations (r's between 0 and 0.30) to all other measures, providing more evidence that the NEBS is not measuring other constructs. Interestingly, other studies evaluating personality traits and paranormal beliefs have been mixed 62,63 , with some studies observing positive correlations with neuroticism 64,65 (unlike our study which found a negligible negative correlation) and others not finding any correlations [65][66][67] . The NEBS reliability and internal consistency was also demonstrated through high Cronbach's alphas for both subscales in two different samples.…”
Section: Discussioncontrasting
confidence: 87%
“…The overall results of the two studies provide psychometric support for the validity and reliability of the NEBS as a brief assessment of self-reported paranormal beliefs and experiences. 62,63 , with some studies observing positive correlations with neuroticism 64,65 (unlike our study which found a negligible negative correlation) and others not finding any correlations [65][66][67] . The NEBS reliability and internal consistency was also demonstrated through high Cronbach's alphas for both subscales in two different samples.…”
Section: Discussioncontrasting
confidence: 84%
“…For instance, Utinans et al ( 2015 ) produced a Latvian Version of the RPBS, which yielded a six-factor structure (Magical Abilities, Psychokinesis, Traditional Religious Belief, Superstition, Spirit Travel, and Extraordinary Life Forms). Additionally, a study using undergraduate students from the University of Zagreb, Croatia (Mikloušić et al, 2012 ), produced a previously unreported three-factor solution. This comprised General Paranormal Belief (mostly Psi and Spiritualism subscale items, with some Precognition, Witchcraft and Extraordinary Lifeforms items); Traditional Religious Belief (Traditional Religious Beliefs scale items); and Rituals and Practices (Superstition subscale items and the remaining Precognition, Witchcraft and Extraordinary Lifeforms subscale items).…”
Section: Introductionmentioning
confidence: 99%